Resonant Raman Scattering in MoS2. Issue 1726 (23rd February 2015) - Gołasa, Katarzyna; Grzeszczyk, Magdalena; Leszczyński, Przemysław; Nogajewski, Karol; Potemski, Marek; Babiński, Adam
ABSTRACT: Resonant Raman scattering in molybdenum disulfide (MoS2 ) is studied as a function of the sample thickness. Optical emission from 1ML, 2ML, 3ML and bulk MoS2 is investigated both at room and at liquid helium temperature. The experimental results are analysed in terms of the recently proposed attribution of the Raman peaks to multiphonon replica involving transverse acoustic phonons from the vicinity of the high-symmetry M point of the MoS2 Brillouin zone. It is shown that the corresponding processes are quenched in a few monolayer samples much stronger than the modes involving longitudinal acoustic phonons. It is also shown that along with the disappearance of multiphonon replica, the Raman modes, which are in-active in bulk become active in a few-monolayer flakes.